Aerodynamic performance analysis of an airborne wind turbine system with NREL Phase IV rotor. (15th February 2017) - Saeed, Muhammad; Kim, Man-Hoe
Highlights: Aerodynamic predictions for a buoyant airborne system at an altitude of 400 m. Aerodynamic characteristics of NREL Phase IV rotor operating in a shell casing. Buoyant shell aerodynamics under varying wind conditions. Abstract: Wind energy becomes more powerful and consistent with an increase in altitude, therefore, harvesting the wind energy at high altitude results in a naturally restocked source of energy which is cheaper and far more efficient than the conventional wind power system. Airborne wind turbine (AWT), one of the many techniques being employed for this purpose, stands out due to its uninterrupted scheme of energy production. This paper presents the aerodynamic performance of AWT system with NREL Phase IV rotor at an altitude of 400 m. Unsteady simulation of the airborne system has been carried out and variations in the rotor's torque for a complete revolution are reported and discussed. In order to compare the performance of the shell mounted configuration of Phase IV rotor with its standard test configuration, steady state simulations of the rotor are also conducted under various wind conditions for both configurations. Finally, for stable design of the buoyant airborne system, aerodynamic forces on the shell body are computed and reported.